Hubungan antara Kesiapan Belajar dengan Hasil Belajar Siswa Kelas V MI Miftahul Ulum Tambakrejo Probolinggo - Salwa Zata Shabrina; Ade Cyntia Pritasari (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
This study aims to analyze the relationship between learning readiness and the cognitive learning outcomes of fifth-grade students at MI Miftahul Ulum Tambakrejo Probolinggo. Learning readiness includes aspects of academic, physical, social, emotional, and cognitive skills, which are believed to influence learning outcomes. The research method used is quantitative with a correlational approach. The research sample consists of fifth-grade students, with data collected through questionnaires and learning outcome scores. Data analysis was conducted using Pearson and Spearman Rank correlation tests to measure the relationship between variables. The results indicate that although there is a positive relationship between learning readiness and learning outcomes in all subjects, the strength of this relationship is very weak. None of the correlations reached the required statistical significance to support the hypothesis of a meaningful relationship. Therefore, it can be concluded that H0 is accepted, meaning that there is no relationship between learning readiness and the cognitive learning outcomes of fifth-grade students at MI Miftahul Ulum Tambakrejo Probolinggo.